2022
DOI: 10.3390/ijerph19020779
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Environmental Impact of Plastic Waste Disposal in South African Townships: A Review

Abstract: Twenty-first century human behaviour continues to escalate activities that result in environmental damage. This calls for environmentally friendly solutions, such as waste recycling and handling, to deal with the increased amount of waste, especially plastics. The plastic materials manufacturing sector is booming, particularly packaging; while only a fraction of its waste is recycled, another fraction is destroyed, and the larger part continues to pollute the environment. In addition to other waste disposal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 63 publications
(63 reference statements)
0
29
0
1
Order By: Relevance
“…The extensive experiments indicated that hydrogen pressure was pivotal in enhancing the liquid product yield, from 69.6 ± 6.2 wt % to 93.9 ± 5. 7 137 examined the biological decomposability of PLA by thermophilic methane fermentation (TMF) and analyzed the microorganisms involved in PLA decomposition. The research utilized disposable cutlery and pure poly L-lactic acid (PLLA) pellets for both small and large-scale batch tests, observing a 70−77% decomposition of PLA by TMF based on weight changes, and CH 4 yield ranged from 321−343 mL CH 4 /g PLA consumed, a significant figure underscoring the potential for methane production from PLA.…”
Section: Biobased Polymers In the Fuel Industrymentioning
confidence: 99%
“…The extensive experiments indicated that hydrogen pressure was pivotal in enhancing the liquid product yield, from 69.6 ± 6.2 wt % to 93.9 ± 5. 7 137 examined the biological decomposability of PLA by thermophilic methane fermentation (TMF) and analyzed the microorganisms involved in PLA decomposition. The research utilized disposable cutlery and pure poly L-lactic acid (PLLA) pellets for both small and large-scale batch tests, observing a 70−77% decomposition of PLA by TMF based on weight changes, and CH 4 yield ranged from 321−343 mL CH 4 /g PLA consumed, a significant figure underscoring the potential for methane production from PLA.…”
Section: Biobased Polymers In the Fuel Industrymentioning
confidence: 99%
“…Mngomezulu [14] and Adeniran [15] identified the typology of municipal waste to include cans, and other metals, paper, bottles, plastics, food remains, old appliances, glass and construction demolition waste, among others.…”
Section: Waste Management Practicesmentioning
confidence: 99%
“…Low-income countries' main waste procedures and disposal mechanisms are open dumping and open burning [13]. For example, open littering [14], open dump [15], illegal dump sites [16], and incineration [17], among others, are some of the waste management practices still in practice in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Bahrain has one of the highest waste generation rates per capita, an annual amount of 1.2 million tons of solid waste is produced by the county yearly [3]. Managing this rapidly growing waste stream cost-effectively and sustainably is a major environmental concern which plays a critical role in the sustainability of economic, social, and environmental factors [4]. Recently, recycling companies had consultations about waste management that support and strengthen the concept of reusing materials.…”
Section: Introductionmentioning
confidence: 99%